Hedging ship price risk using freight derivatives in the drybulk market - Roar Adland; Haakon Ameln; Eirik A. Børnes (Journal of Shipping and Trade (JST), 2020)
We show that a fixed-maturity time-weighted Forward Freight Agreement (FFA) portfolio should be used to proxy the expected future earnings of a vessel. We investigate the corresponding hedging efficiency when using a portfolio of FFA prices to hedge ship price risk of both static hedge ratios calculated using Ordinary Least Squares estimation and the dynamic hedge ratios generated from a dynamic conditional correlation GARCH (1,1) model. We find that the hedging efficiency is greater for newer vessels than older vessels and that the static hedge ratio outperforms the dynamic hedge ratio. Our work is an extension of earlier empirical work which has only considered the hedging efficiency of varying-maturity calendar FFA contracts for a single vessel age.
Keywords: 650; Ship values; FFA; Hedging efficiency; Hedge ratio